Development of Photonovela with Character Education: As an Alternative of Physics Learning Media - Ariyani, Farida; Nayana, Taras; Saregar, Antomi; Yuberti, Yuberti; Pricilia, Agitha (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
The internalization of character education in science learning through a variety of learning media has been researched recently, one of which is through the photonovela media which is the medium of insertion of character values in learning material. The focus of this research is; 1) developing photonovela learning media with character education on work material and energy, 2) knowing photonovela media feasibility as a supplement to physics learning with character education on work material and energy 3) knowing the response of students to photonovela media with character education in an energy material. This research is a Research and Development study adopted the development of Borg and Gall with the subject of junior high school students. The research instruments used were questionnaires by material experts, media experts, and junior high school physics teachers and questionnaires for students' responses in the three schools. The results of the assessment by material experts obtained a percentage of 85%, the assessment of media experts was 90%, and the assessment of junior high school teachers was 84.16%, while the response of students in three junior high schools was 87.6%, 94%, and 93.6%. In conclusion, this study produced a product in the form of appropriate photonovela media as a supplement to physics learning with character education on business material and energy